2018
DOI: 10.1051/e3sconf/20185900023
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic characteristic of selected installation valves installed on various pipes materials

Abstract: Presented studies covered determination of minor pressure losses and values of minor loss coefficients for two selected installation valves: water control globe valve and angle valve, both DN 15. The tested valves were installed on three pipes, including PP 20x3.4 mm, PEX-Al-PEX 16x2.0 mm and Cu 15x1.0 mm. In order to reflect the real operating conditions of the angle valve, the elastic PVC pipe was used. Our researches were performed on the laboratory installation, for the variable flow rate. The obtained res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It should also be noted that the devices of each market have their constructive, geometric, and material characteristics normally used, thus, there is an intrinsic imprecision when transferring international research and technical results. Another difficulty is that, as shown by Poręba et al (2018), the minor head loss in valves can be influenced by the piping material in which they are installed, as well as by the set of couplings used in the test apparatus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that the devices of each market have their constructive, geometric, and material characteristics normally used, thus, there is an intrinsic imprecision when transferring international research and technical results. Another difficulty is that, as shown by Poręba et al (2018), the minor head loss in valves can be influenced by the piping material in which they are installed, as well as by the set of couplings used in the test apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the vertical axis of Figure5Dshows that the scale of the K value was much larger than those obtained for the other openings. According toRazaey (2020), in the initial stages of valve opening, the rate of change in the head loss coefficient is very pronounced, thus explaining this discrepancy.With their work,Poręba et al (2018) evaluated minor head losses coefficients for DN 15 angle and globe valves, for variable degrees of closure and different values of flowrate, as was done in this research. Their results showed a dependence between the head loss and coefficients with the degree of valve closure, in the same way as detected in this study, and as the tested valves had different construction, the authors also found significant differences between the head loss for angle and globe valves for the same opening/closure degree.…”
mentioning
confidence: 99%
See 1 more Smart Citation